Presence and recurrence of Paremias in the Peruvian traditions of Ricardo Palma - Valdivia Paz-Soldán, Rosario (2019)
Ricardo Palma is an author that deserves to be read, analysed, studied and translated several times. From many years now literary critics and researchers have been interested in studying the work of our traditionist from various approaches. Our paper is focused in analysing the proverbs from five traditions of Ricardo Palma.